Highly Dispersed Cu−NX Moieties Embedded in Graphene: A Promising Electrocatalyst towards the Oxygen Reduction Reaction. Issue 21 (22nd August 2018) - Lu, Xiangyu; Du, Lei; Wang, Dan; Yang, Peixia; Liu, Lilai; Zhang, Jinqiu; An, Maozhong; Levin, Oleg; Wang, Jinpeng; Ge, Liping
Abstract: Transition metal–carbon–nitrogen catalysts for the oxygen reduction reaction (ORR) are promising and challenging. Cu is a potential transition metal to form efficient ORR catalysts for fuel cells. Herein, a facile method is developed to synthesize a highly dispersed Cu−NX and N‐doped graphene (Cu−N−G) catalyst. The Cu−N−G catalyst shows a half‐wave potential ( E 1/2 ) of 0.859 V, which is comparable to the commercial Pt/C catalyst (0.856 V), and is among the best compared with the previously reported Cu‐based materials. In addition, such a catalyst shows good stability and methanol tolerance in alkaline media. A synergy of doped N (pyridinic and graphitic N) and Cu−NX moieties as well as the pore structure are revealed to account for the enhanced ORR activity. Abstract : Top cop : A highly dispersed Cu−NX and N‐doped graphene (Cu−N−G) catalyst is prepared by pyrolyzing a composite of graphene oxide, urea, and copper (II) acetate monohydrate. After acid leaching, highly dispersed Cu−NX moieties embedded in N‐doped graphene are confirmed by HAADF‐STEM imaging and corresponding elemental mapping. The Cu−N−G catalyst shows a half‐wave potential comparable to the commercial Pt/C catalyst, and is among the best when compared with the previously reported Cu‐based materials.